Impact of additive manufacturing on titanium supply chain: Case of titanium alloys in automotive and aerospace industries - Patricia Nyamekye; Saeed Rahimpour Golroudbary; Heidi Piili; Pasi Luukka; Andrzej Kraslawski (Advances in Industrial and Manufacturing Engineering, 2023)
Additive manufacturing (AM) is a promising technology for designing complex metallic pieces for different sectors with resource and time effectiveness. Titanium (Ti) is an essential critical material for AM development. AM can produce intricate and cost-effective components with Ti alloys for the transportation sector which would not be possible with conventional manufacturing (CM) technologies. This study assesses the impact of AM on the life cycle of Ti and its alloys by using review (numerical data, case examples) and dynamics simulation modelling. This article quantifies potential environmental benefits and examines aspects related to using Ti alloys in the automotive and aerospace industries. Mass flow, energy consumption and related greenhouse gas (GHG) emissions are assessed by making a comparison between subcategories of AM including binder jetting (BJT), directed energy deposition (DED), electron beam-based powder bed fusion (EB-PBF), and laser-based powder bed fusion (L-PBF) and CM processes including forging, milling, machining, and die casting. The results show that the AM subcategories considered potentially reduce manufacturing phase energy consumption and GHG emissions except for L-PBF. The findings highlight that an inclusive consideration of all life cycle phases is needed to fully identify potential benefits of AM for industries. Also, the scenario analysis in this study proposes the opportunity for saving mass and minimizing energy consumption and GHG emissions by optimizing the structural design and manufacturing processes for Ti components.